Spectrum of Neurological Disorders in Neurology Outpatients Clinic in Tertiary Care Hospital: A Cross Sectional Study - Muhammad Omer Pasha, Zahra Fayyaz, Qurrat Ul Ain Naqvi, Saba Saleem, Sikandar Javed Bajwa, Tehreem Ghani (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Neurological disorders are one of the most noticeable causes of morbidity and mortality that have a negative impact on patient’s lifestyle. A significant rate of these diseases exists in developing populations. However, there is lack and shortage of literature on neurological illnesses in Pakistan. This study was therefore carried out to determine the pattern of neurological diseases in this setting which can also provide a benchmark for planning and care for neurological illnesses at tertiary care level. Methodology: This is a Descriptive cross-sectional review conducted at the neurology outpatient clinic of the Lahore General Hospital, Lahore over the duration of 9 months between April, 2021 and December, 2021. Data was gathered through a predesigned questionnaire from the patients which included data regarding gender, age, marital status, occupation, residential status and affected disease. Results: Among all patients (140) who visited the neurology clinic over this duration, the most frequent neurological disorder was migraine (40%), followed by stroke (25%) and seizures (20%). The major age group that visited the neurology clinics was between 51 and 60 years (30%) and among them, most were males (60%). Conclusion: Stroke, migraine, and Parkinson’s disease were the most common neurological disorders among participants of present study. Neurological diseases outnumber other diseases in Pakistan, affecting all age groups and genders. Headache, migraine, stroke, and seizure were found to be more common than AD and other dementias in Western countries and as significant reasons of morbidity. Keywords: Neurological disorders, neurology clinic, outpatients